1996
DOI: 10.1007/bf02246017
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in plasma cocaine levels and subjective effects after acute cocaine administration in human volunteers

Abstract: Gender differences after acute cocaine administration have received little attention in spite of the fact that males and females respond differently to many drugs. Seven male and seven female occasional cocaine users received both an intranasal dose of cocaine hydrochloride (0.9 mg/kg) and placebo powder in a randomized order and reported subjective effects via an instrumental joystick device and various questionnaires. Blood samples were withdrawn at 5-min intervals to assess pharmacokinetic differences. Male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
134
7
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(166 citation statements)
references
References 42 publications
23
134
7
2
Order By: Relevance
“…These results are consistent with those reported by others (Kosten et al 1996;Lukas et al 1996;Haney et al 1998) despite differences in route of administration, acute versus repeated dosing, or both. For example, women reported lower ratings of "Stimulated" and dose quality than men following repeated doses of intravenous cocaine (Haney et al 1998).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are consistent with those reported by others (Kosten et al 1996;Lukas et al 1996;Haney et al 1998) despite differences in route of administration, acute versus repeated dosing, or both. For example, women reported lower ratings of "Stimulated" and dose quality than men following repeated doses of intravenous cocaine (Haney et al 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Similar conclusions were reached by and Haney et al (1998). In contrast, Lukas et al (1996) concluded that women were more sensitive to the cardiovascular effects of cocaine, because although men had higher cocaine plasma concentrations than women, there were no sex differences in heart rate following a single dose of 0.9 mg/kg intranasal cocaine. However, inspection of the data and figures in that study shows a clear tendency for heart rate to be higher in men than in women; the failure to reach statistical significance may be a result of the small sample size and the relatively low cocaine dose.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations